Age-dependence of Poly(Adenosine Diphosphate-Ribos)yl Polymerase 1 Inhibition in Liver and Thymocyte Nuclei after the Treatment of Rats with Cisplatin - Asatryan, Anush (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: Poly(ADP-ribos)yl polymerase 1 (PARP1) inhibitors enter into clinical trials for mono and combination cancer chemotherapy, improving curative potential of DNA-alkylating agents. It is documented that therapeutic outcomes after the treatment of patients with broad spectrum of drugs are age-dependent and reveal sexual dimorphism. We investigated age- and sex-dependent differences in PARP1 inhibition by benzamide (Bam) and adenosine triphosphate (ATP) in rat liver and thymocyte nuclei after the treatment of rats with cisplatin. Materials and Methods: The drug was injected intraperitoneal. Animals were treated according to the regulations of National Centre of Bioetics (Armenia). Cell nuclei were isolated according to the standard procedure. PARP 1 activity was evaluated by nicotinamide adenine dinucleotide (NAD)+ consumption. Data are expressed as mean ± S.D. Statistical differences in the results between groups were evaluated by the Student’s t-test. A probability (P) value of <0.05 was considered significant. Key results: Basal PARP 1 activity in rat thymocyte and liver nuclei decreases in the period of animal growth from 6 to 10 weeks. The treatment of intact rat with cisplatin differentially affected PARP 1 activity in liver and thymocyte nuclei. It was shown that efficiency of PARP1 inhibition in thymocyte and liver nuclei by Bam and ATP is age-dependent phenomenon which is affected by in vivo treatment of intact rat with cisplatin. It is suggested that the design of personalized combination therapy regimen should consider cisplatin induced age-dependent changes in PARP 1 inhibition by competing/allosteric inhibitors.